Pharmacoeconomic Evaluation and Clinical Outcomes of Channa as an Adjuvant to 20% Human Albumin Therapy in Patients with Chronic Kidney Disease: A Cost-Effectiveness Analysis (CEA) at Imelda Pekerja Indonesia General Hospital - Alex Handani Sinaga; Martalena Zebua; Guntur Berlian; Asep Aripin (Jurnal Teknik Indonesia, 2026)
Hypoalbuminemia is a common complication in patients with Chronic Kidney Disease (CKD) and is associated with increased morbidity, mortality, and length of hospital stay. Human albumin therapy is effective but costly; therefore, pharmacoeconomic evaluation of alternative therapies based on snakehead fish (*Channa striata*) extract is warranted. This study aimed to evaluate the cost-effectiveness and clinical outcomes of Channa as an adjuvant to 20% Human Albumin therapy in CKD patients with hypoalbuminemia at Imelda Pekerja Indonesia General Hospital, Medan. A descriptive observational study with retrospective data collection was conducted involving 35 patients who were divided into three treatment groups: Channa product, 20% Human Albumin, and a combination of both therapies. Effectiveness was assessed based on the increase in serum albumin levels (Δ albumin, g/dL), while costs were calculated based on direct costs of albumin therapy. Cost-effectiveness analysis was performed by calculating the Average Cost-Effectiveness Ratio (ACER) and Incremental Cost-Effectiveness Ratio (ICER). The results showed that the total direct cost of albumin therapy was IDR 57,970,200, with the lowest cost observed in the Channa product group. The Channa product group had the lowest ACER (IDR 990,889 per g/dL), and the ICER analysis indicated that Channa was a dominant strategy, being both less costly and more effective. It was concluded that Channa therapy was the most cost-effective option for correcting hypoalbuminemia in CKD patients, while 20% Human Albumin remained important for severe conditions requiring rapid correction.